Hazard identification, risk assesment and risk control serta penerapan risk mapping pada rumah sakit hewan Prof. Soeparwi Universitas Gadjah Mada - Pertiwi Pertiwi; Yudha Nurhantari; Santosa Budihardjo (Berita Kedokteran Masyarakat (BKM), 2019)
Hazard identification, risk assesment and risk control and the application of risk mapping at Hospital of the Animal Prof. Soeparwi Universitas Gadjah Mada Purpose: This research was held to analyze the work accident using HIRARC method and the applied of Risk Mapping at the hospital of the animal of Prof. Soeparwi Gadjah Mada University, Yogyakarta.Method: This research used descriptive qualitative research method. The qualitative method used to describe the condition, assess, and to recognize the work accident analysis. The data used was grabbed from Hazard Identification Risk Assessment and Risk Control (HIRARC) method and questionnaire.Results: Hazard identification used HIRARC method at the hospital of the animal of Prof. Soeparwi Gadjah Mada University was about 198. The work hazard commonly includes physical hazard, chemistry, biologist, ergonomics, and psychosocial. The risk assessment which held denoted that there were 61 low risks, 108 medium risks, and 15 high risks. The recommendations of risk restraint that can be given were technician control, administrative, and the use of personal protective equipment (PPE).Conclusion: HIRARC method had been applied at the hospital of animal of Prof. Soeparwi with the result to that grooming unit was high risk work place, assessed with risk mapping. The risk was from animal contact phisically.